2014
DOI: 10.1002/er.3215
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced photocatalytic hydrogen production under visible light over a material based on magnesium ferrite derived from layered double hydroxides (LDHs)

Abstract: The magnesium ferrite derived from layered double hydroxides (molar ratio Mg/Fe = 2), synthesized by coprecipitation method is found to be an active photocatalyst for hydrogen production from water under visible light. The structural, morphological, and optical properties of the material are characterized by powder X-ray diffraction, scanning electron microscopy, and Fourier transform infrared and UV-Vis diffuse reflectance spectroscopy. The results indicated that the material has small particles with a diamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Regarding ferrites of non-transition metals, some alkaline and alkali earth metal ferrites have been tested for photocatalytic hydrogen evolution. For example, Boudjemaa and co-workers synthesized the MgFe2O4 spinel ferrite by calcination of a Mg-Fe layered double hydroxide obtained by co-precipitation [138]. This material gave rise to hydrogen evolution under visible light from an aqueous sulphite solution, although production declined after 20 min of reaction.…”
Section: Single-phase Ferrite Photocatalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding ferrites of non-transition metals, some alkaline and alkali earth metal ferrites have been tested for photocatalytic hydrogen evolution. For example, Boudjemaa and co-workers synthesized the MgFe2O4 spinel ferrite by calcination of a Mg-Fe layered double hydroxide obtained by co-precipitation [138]. This material gave rise to hydrogen evolution under visible light from an aqueous sulphite solution, although production declined after 20 min of reaction.…”
Section: Single-phase Ferrite Photocatalystsmentioning
confidence: 99%
“…Pioneer work on the fundamental investigation using ferrites as electrodes in (photo) electrochemical reactions dates back to the late 1970s and early 1980s and has continued in the following years, including different compositions. P-type CaFe2O4 [123][124][125][126][127][128][129][130], CdFe2O4 [131], p-and ntype CoxFe3−xO4 and CoTixFe2−xO4 [132], p-type CoFe2O4 [133], p-and n-type NiFe2O4 [134,135], Li0.5Fe2.5O4 [136], MgFe2O4 [137,138], TixFe3−xO4 [139] and n-type ZnFe2O4 [136][137][138][139][140][141][142] are remarkable examples.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the catalytic performance is highly correlated with the metal dispersion, the support properties, and the metal‐support interaction. Layered double hydroxides (LDHs) are a class of layered materials with the formula [M 2+ 1 − x M 3+ x (OH) 2 ]( A n− ) x/n ·mH 2 O . Recently, LDHs have received considerable interest in a large number of fields, including adsorption, catalysis, and water purification originating from their high specific surface area (SSA), unique structure, and highly tunable composition.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, researchers have shown a keen interest in the nanocrystalline metal-ferrite (MFe 2 O 4 ) systems owing to their peculiar physical and chemical properties [1], because of the contribution of Fe-d orbitals above the valence band. They exhibit tremendous potential towards their technological application in various fields such as pigments, magnetic recording, magnetic resonance imaging, sensors, ferrofluids and photocatalysis [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. The physicochemical properties and applications of these nanomaterials are strongly correlated to their crystallinity, size and size distribution.…”
Section: Introductionmentioning
confidence: 99%